Populating the novel : literary form and the politics of surplus life - Steinlight, Emily, 1979- (Cornell University Press, 2018)
From the teeming streets of Dickens's London to the households of domestic fiction, nineteenth-century British writers constructed worlds crammed beyond capacity with human life. In Populating the Novel, Emily Steinlight contends that rather than ...